Topical aspirin provides protection against galactosemic cataract - Gupta Suresh (Indian Journal of Ophthalmology, 1997)
Effect of twice daily administration of aspirin eyedrops on the onset and progression of cataract induced by 30% galactose diet was studied. On the 30th day of galactose feeding while all control group rats showed complete stage IV opacity, those receiving aspirin eyedrops showed only mild cataractous changes of stage I. In vitro studies showed that addition of aspirin to the medium significantly decreased dulcitol formation (p < 0.01) and maintained glutathione levels (p < 0.02). Intraocular penetration studies using isolated goat cornea showed excellent penetration by salicylate indicating feasibility of topical administration. The results of the present study demonstrate that topical aspirin possesses significant anticataract activity in galactosemic cataract.